A SIMPLE HPLC METHOD FOR IN-VITRO DISSOLUTION STUDY OF SERTRALINE HYDROCHLORIDE IN TABLETS: Pharmaceutical Science-Chemistry - SUSHIL P. NARKHEDE; SANTOSH KUMAR SINGH; G. VIDYASAGAR (International Journal of Life Science and Pharma Research, 2022)
The main aim of present work was to develop and validate a dissolution test for Sertraline Hydrochloride in tablets using HPLC method. The dissolution established conditions were: 900 ml of 0.05M Acetate buffer pH 4.5 as dissolution medium, using a paddle apparatus at a stirring rate of 75 rpm. The chromatographic condition employed a C-18 column (Eurospehere, 250 x 4.6mm, 5µm), isocratic elution with Acetonitrile:Methanol:Phosphate buffer pH 3 (20:50:30 V/V/V) and UV detection at 274 nm. The method was validated to meet requirements for a global regulatory filing. The dissolution test developed was adequate for its purpose and could be employed for routine quality control of Sertraline Hydrochloride tablets.